Quantitative Comparison of Five Different Photosensitizers for Use in a Photopolymer. (12th September 2012) - Qi, Yue; Gleeson, Michael R.; Guo, Jinxin; Gallego, Sergi; Sheridan, John T.
Abstract : Several studies of the time varying photon absorption effects, which occur during the photoinitiation process involving in photopolymer materials, have been presented. Three primary mechanisms have been identified: (i) the dye absorption, (ii) recovery, and (iii) bleaching. Based on an analysis of these mechanisms, the production of primary radicals can be physically described and modelled. In free radical photopolymerization systems, the excited dye molecules induce the production of the primary radicals, R, which are key in determining how many monomers are polymerized. This, in turn, is closely related to the refractive index modulation formed during holographic recording. In this paper, to avoid the complexities involved in estimating the rate constant of intersystem crossing, k s t, in going from the excited singlet state dye to the excited triplet state dye, we introduce two rates, k a S and k a T these are the proposed rate constants of photon absorption in going from the ground state to the singlet and triplet states, respectively. Using the resulting model, four kinds of Xanthene dyes: Erythrosin B; Eosin Y; Phloxine B, Rose Bengal, and one Thiazine dye: Methylene Blue, are experimentally characterised for use in an AA/PVA photopolymer.